PREDICTION OF THE FUTURE: NEW ROLES OF THE UNIVERSITY LIBRARIAN - NIKOLAIENKO, Nataliia M.; RYBALCHENKO, Olena M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
Objective. The article analyzes the new roles of librarians - facilitator, tutor, moderator, presents their introduction into the activities of the university library, reveals the impact of innovations on the effectiveness of the library and the university. Methods. The study was conducted by reviewing publications related to clarifying the new roles of librarians in the practice of modern university libraries, summarizing the experience of the Scientific Library of Kharkiv Petro Vasylenko National Technical University of Agriculture (SL KhNTUA) to introduce new activities. Results. During the study, the authors determined that the SL KhNTUA’ introduction of the innovative forms in terms of new roles of librarians (facilitator, tutor, moderator) contributes to the development and diversification of library services, increase in the role of SL as an active partner of the university in research, teaching and educational work; emphasizes and strengthens the role of the library in raising the ranking of the university. Conclusions. The originality of the work is to expand ideas about the new roles of librarians in the activities of the university library, which is an important factor in assessing the effectiveness of its management. Practical value. The obtained results are used to improve the management of human resources of university libraries.